Students’ Participation in Learning English at Eighth Grader of Junior High School - Hervina; Desfi Yenti (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2023)
In learning English, students need to participate in all kinds of activities. Student participation is an interaction between teacher and student. This is reflected in the active participation of students in the teaching and learning process. Researchers are interested in analyzing students' engagement in learning English. The design of this study was a qualitative study. The purpose of this study was to examine how students are involved in learning English. The participant in this study was the 8th grade student at SMP N 9 Payakumbuh. Samples were selected by using a sampling technique. The data sources for this study were observations and questionnaires. Data were analyzed using the following several steps; Data management, reading/annotating, classification, interpretation, reporting. Data analysis showed that most students engaged in verbal instruction and received less non-verbal instruction. The results of the questionnaire determined the highest (1555) and lowest (1390) nonverbal total scores. In other words, there was a difference between the questionnaire results and the observation results. This assumption that most students did not fill out the questionnaire honestly and ended the video observation could not be articulated because they only completed the task during the observation